1975
DOI: 10.1295/polymj.7.86
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Benzophenone Eetyl as an Initiator of Anionic Polymerization of Methyl Methacrylate

Abstract: The anionic polymerization of methyl methacrylate in tetrahydrofuran initiated by sodium-benzophenone ketyl was studied in rigorously purified systems by means of optical absorption measurements as well as conventional polymerization techniques to elucidate the initiation process involved. It was concluded, on the basis of kinetic behavior of the ketyl anion in reacting with the monomer and the UV absorption of the product polymer, that the addition of the ketyl anion to the monomer forms a propagating carbani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1975
1975
1980
1980

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…By determining the concentration of the former ketyl in the THF solution relative to that of the latter, it was found that the solution of 1.2 x 10 20 spinsjl of magnesium-benzophenone ketyl gave an optical density of 0.888 at 610 nm for a 0.5 em optical path. Thus, the extinction coefficient of the magnesium-benzophenone ketyl was determined to be 18,000 M-1 cm- 1 • Throughout the present investigation, the concentration of the initiator was determined by doubling the concentration of the magnesium ketyl obtained on the basis of this extinction coefficient. Figure 2 shows the Beer-Lambert plot for the ketyl at the absorption maximum at 610 nm.…”
Section: / /mentioning
confidence: 91%
See 4 more Smart Citations
“…By determining the concentration of the former ketyl in the THF solution relative to that of the latter, it was found that the solution of 1.2 x 10 20 spinsjl of magnesium-benzophenone ketyl gave an optical density of 0.888 at 610 nm for a 0.5 em optical path. Thus, the extinction coefficient of the magnesium-benzophenone ketyl was determined to be 18,000 M-1 cm- 1 • Throughout the present investigation, the concentration of the initiator was determined by doubling the concentration of the magnesium ketyl obtained on the basis of this extinction coefficient. Figure 2 shows the Beer-Lambert plot for the ketyl at the absorption maximum at 610 nm.…”
Section: / /mentioning
confidence: 91%
“…was typically 2). 1 It should be noted that the value as high as 2. 7 is obtained for the ratio of the number of polymer chains to the number of the initiator fed.…”
Section: Polymerizationmentioning
confidence: 99%
See 3 more Smart Citations